Analysis of the Impact of Artificial Intelligence Technology on Art Elements and Originality Aspects of Graphic Design State Polytechnic of Creative Media - Siagian, Rismala Laurensia; Aisyah, Siti; Marbun, Erie Zeklyn; Saitapy, Maulana; Banjarnahor, Yoshea Febriani (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
In the use of Artificial Intelligence in Graphic Design which has a positive and negative impact on designers. Some of the benefits felt by graphic designers who use Artificial Intelligence are in the efficiency and speed of the design process, as well as AI can provide advice and assistance in enhancing design creativity, and can also assist in adjusting the Ai user reference itself through analyzing the data provided by the designer. AI can also have a negative impact, which can provide concern where AI can replace the role of the designer himself. In addition, it has an impact on the quality of design which can potentially reduce the value of design services. The use of AI can increase the risk of plagiarism in the work produced. In the art element, the use of AI is often considered less original because it only relies on modifying existing images. It is not a more in-depth creative process. Therefore, designers need to balance the use of AI technology, to maintain creativity in their work. The purpose of this research as a graphic designer is to analyze how the impact of graphic design production if it uses Artificial Intelligence which is very rapidly developing today.